Effect of graphite particles as additive on the curing behaviour of β-tricalcium phosphate suspensions and scaffold fabrication by digital light processing. Issue 12 (September 2020) - Wu, Yanlong; Chen, Ruomeng; Zhao, Guangbin; Chen, Xu; Qu, Xiaoli; Liu, Yaxiong
Abstract: Reducing the viscosity of high solid-loading ceramic suspensions and controlling the resolution of ceramic green parts produced by digital light processing (DLP) 3D printing are two important concerns in the ceramic additive manufacturing industry. The presence of ceramic particles within a photopolymerizable system leads to light scattering that reduces the resolution of the ceramic green scaffolds. This study introduced a graphite additive to solve these problems and focused on the effects of graphite concentration on the viscosity, curing behaviour and scaffold fabrication of β-TCP ceramic suspensions. As a result, it was found that an appropriate addition of graphite reduced the viscosity of the ceramic suspensions, and the light scattering decreased with the increase of graphite concentration. Both the cure depth (Cd ) and excess width (Cex ) also decreased with the increase of graphite concentration. But, graphite has a larger effect on the width curing than depth curing.